An in vitro investigation of the inhibitory mechanism of β-galactosidase by cinnamaldehyde alone and in combination with carvacrol and thymol - Wang, Lang-Hong; Wang, Man-Sheng; Zeng, Xin-An; Gong, De-Ming; Huang, Yan-Bo (Biochimica et biophysica acta. General subjects, 2017)
Some antibacterial agents exert their antimicrobial action by targeting the cytoplasmic macromolecules, such as proteins or nucleic acids, to disturb the properties of macromolecules that may deeply influence their biological activities and functions. Cinnamaldehyde (CIN) is a natural antibacterial ingredient found in the bark and leaves of cinnamon trees. The inhibitory mechanism of a typical enzyme, β-galactosidase by CIN was investigated by UV–visible, fluorescence, 3-D spectroscopy, circular dichroism, atomic force microscopy and molecular modeling studies. CIN decreased the activity of β-galactosidase by competitive inhibition through a multiphase kinetic process. 3-D spectroscopy and circular dichroism showed that the binding of CIN to β-galactosidase resulted in changes in micro-environment of tryptophan and tyrosine residues, and conformation of β-galactosidase. The molecular recognition was also analyzed through modeling which indicated that CIN was inserted into the active site pocket of β-galactosidase and interacted with amino acid residues, such as Met502, Trp568, Phe601 and Trp999. Atomic force microscopy showed that a serious destabilization of the native conformation of β-galactosidase occurred after binding with CIN, e.g., morphological changes and increased dimensions of the β-galactosidase molecule. Moreover, it was found that the combinations of CIN, carvacrol and thymol exposure displayed synergistic effects on the inhibition of β-galactosidase. This study exhibits a comprehensively understanding about the action mechanism of CIN that affects the conformation and activity of β-galactosidase in biochemical processes and provides some new insights into the possible intracellular targeting behaviors of CIN at a molecular level. Cinnamaldehyde occupies the active site of β-galactosidase to decrease the activity and alter the secondary structure of this enzyme. [Display omitted] •CIN decreased the β-gal activity by competitive inhibition via a multiphase process.•Binding of CIN to β-gal resulted changes in the secondary structure of β-gal.•CIN inserted into the active site of β-gal and interacted with amino acid residues.•AFM revealed that morphological changes and increased dimensions of the β-gal by CIN.